RETRACTED: Regulation of thermal physical properties multicomponent building materials - Salimjonov Jasurbek; Mamatov Khamidulla; Karimova Mukhtasar; Abdullayev Ulugbek; Nigmatov Ulugbek; Yusupov Abdulkhamid; Otakulov Bakhromjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001